Studi Komparatif Literasi Digital Karyawan Bank: Analisis Dampak Perbedaan Spesifikasi Perbankan - Gusti, Triningtyas Elisabeth Putri; Caroline, Angela; Kornarius, Yoke Pribadi; Gunawan, Agus (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The rapid technological evolution in banking poses novel challenges for service delivery. Banks must navigate innovation to stay competitive, yet achieving impactful innovation requires harmonizing innovative work behavior that bridges conceptual and practical aspects. This pertains especially to relevant product and service development. Technology's pivotal role in banking underscores the need for improved digital literacy. This research explores the correlation between digital literacy and innovative work behavior via causal analysis. Surveys and questionnaires garnered participant input on digital literacy and innovative tendencies. Rigorous analysis, including simple linear regression, revealed digital literacy's significant impact on innovative work behavior. Furthermore, variations arise in employee responses across three banks, influenced by size, type, location, and selection processes. The study underscores adapting internal banking policies for digital literacy, aligning with operational demands.